2017
DOI: 10.1038/srep43081
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic effect of atmospheric-pressure dielectric barrier discharge on human colorectal cancer cells via regulation of Sp1 transcription factor

Abstract: Human colorectal cancer cell lines (HT29 and HCT116) were exposed to dielectric barrier discharge (DBD) plasma at atmospheric pressure to investigate the anticancer capacity of the plasma. The dose- and time-dependent effects of DBDP on cell viability, regulation of transcription factor Sp1, cell-cycle analysis, and colony formation were investigated by means of MTS assay, DAPI staining, propidium iodide staining, annexin V–FITC staining, Western blot analysis, RT-PCR analysis, fluorescence microscopy, and anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…In this study, we confirmed the anti-tumor effects of PAM on endometrial cancer. Furthermore, previous studies regarding the direct exposure of NEAPP have demonstrated that the anti-tumor effects are due to mechanisms such as the induction of apoptosis, the inhibition of migration and invasion, and the promotion of cell cycle arrest 20,21 . Although we previously reported that PAM effectively inhibits ovarian cancer plantation in human peritoneal mesothelial cells, the mechanism of the anti-tumor effects of PAM is unclear compared with that of the direct exposure of NEAPP 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed the anti-tumor effects of PAM on endometrial cancer. Furthermore, previous studies regarding the direct exposure of NEAPP have demonstrated that the anti-tumor effects are due to mechanisms such as the induction of apoptosis, the inhibition of migration and invasion, and the promotion of cell cycle arrest 20,21 . Although we previously reported that PAM effectively inhibits ovarian cancer plantation in human peritoneal mesothelial cells, the mechanism of the anti-tumor effects of PAM is unclear compared with that of the direct exposure of NEAPP 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Dual luciferase reporter assay and western blotting showed that Sp1 was a target gene of miR-202. Sp1 is a transcription factor that exists widely in the nucleus and plays an important regulatory role in the occurrence and development of tumors (25). The positive expression rate of Sp1 is higher in cancer patients compared with healthy controls (26).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, plasmas generated at ambient pressure have received great attention as a multidisciplinary topic due to their complexity, and there has been a dramatic increase in plasma applications. Recent publications clearly demonstrate possible utilizations of atmospheric-pressure plasmas and their outstanding results 9 12 . In most applications, various plasma sources are used as generators of reactive chemical species because the contribution of plasmas to processing targets is dominated by chemical reactions.…”
Section: Introductionmentioning
confidence: 97%